2020
DOI: 10.1021/acs.inorgchem.0c00561
|View full text |Cite
|
Sign up to set email alerts
|

NHC Core Phosphonium Ylide-based Palladium(II) Pincer Complexes: The Second Ylide Extremity Makes the Difference

Abstract: The coordinating properties of NHC (A), phenolate (B) and phosphonium ylide (C) moieties have been investigated systematically through the preparation of a family of NHC, phosphonium ylide-based pincer ligands where the third donor extremity can be either a NHC, a phenolate or a phosphonium ylide. The overall donor character of such ligands [NHC(AaBbCc)] (a + b + c = 2) has been analyzed by comparison of the MOs (energy and shape), oxidation potentials (Ep ox), and IR nCO and nCN stretching frequencies of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 73 publications
6
40
0
Order By: Relevance
“…With the previous cases 47-48, the Pd(II) complex 52 constitutes one of the very rare examples of NHC core pincer complex of LX2-type exhibiting two different peripheral coordinating extremities reported to date [93]. The latter, featuring pending phenolate and phosphonium ylide moieties, was readily obtained from the ortho-metallated Pd complex 51 in 94% yield, thanks to the selective acid cleavage of a Car-Pd bond using HOTf in MeCN (Scheme 18).…”
Section: With Co-coordinating Atomsmentioning
confidence: 89%
See 4 more Smart Citations
“…With the previous cases 47-48, the Pd(II) complex 52 constitutes one of the very rare examples of NHC core pincer complex of LX2-type exhibiting two different peripheral coordinating extremities reported to date [93]. The latter, featuring pending phenolate and phosphonium ylide moieties, was readily obtained from the ortho-metallated Pd complex 51 in 94% yield, thanks to the selective acid cleavage of a Car-Pd bond using HOTf in MeCN (Scheme 18).…”
Section: With Co-coordinating Atomsmentioning
confidence: 89%
“…The electronic properties of these phosphonium ylide-based pincer Pd(II) complexes were exploited in homogeneous catalysis for the Pd-catalyzed allylation of aldehydes. It was in particular observed that the Pd complex bearing the most donor pincer ligand, namely the NHC, bis(ylide), wasthe most active in this catalytic process [93].…”
Section: With Co-coordinating Atomsmentioning
confidence: 98%
See 3 more Smart Citations